Venting in Closed Femoral Nailing: A Simple Technique Using a Frazier Suction Tip - Theerawoot Tharmviboonsri; Kongkhet Riansuwan; Rapin Phimolsarnti; Banchong Mahaisavariya (Siriraj Medical Journal, 2020)
A surgical technique to drain the medullary content during closed femoral nailing by using a Frazier suction tip as a vent is demonstrated. This method is simple, safe and reproducible. The medullary content can be drained outside without surrounding soft tissue contamination and the intramedullary pressure is possibly minimized when femoral canal reaming and nail insertion is performed.